2008
DOI: 10.1080/10826080802237928
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Use of Gamma Hydroxybutyrate: Driving Under the Influence

Abstract: Focus group discussions elicited descriptive experiences of driving under the influence of gamma hydroxybutyrate (GHB), and uncovered motivations that led participants to decide whether to get behind the wheel after ingesting this illegal psychoactive substance. Of the 51 current and past users interviewed, average age 31.1 +/- 7.7 years, 40% were female. All were recruited from the San Francisco Bay Area, in 2004. Factors making users vulnerable to adverse complications of driving while under the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…[49 -51] Most subjects reported that they would use GHB again despite severe negative consequences. [53] The impact of GHB on several aspects of sexuality (increased desire and arousal, decreased inhibition, greater willingness to engage in sexual activity) is clearly recognized by all users, but the risk of unsafe sexual practices and sexually transmitted diseases is not appreciated. [53] The impact of GHB on several aspects of sexuality (increased desire and arousal, decreased inhibition, greater willingness to engage in sexual activity) is clearly recognized by all users, but the risk of unsafe sexual practices and sexually transmitted diseases is not appreciated.…”
Section: Gamma-hydroxybutyrate (Ghb)mentioning
confidence: 99%
See 1 more Smart Citation
“…[49 -51] Most subjects reported that they would use GHB again despite severe negative consequences. [53] The impact of GHB on several aspects of sexuality (increased desire and arousal, decreased inhibition, greater willingness to engage in sexual activity) is clearly recognized by all users, but the risk of unsafe sexual practices and sexually transmitted diseases is not appreciated. [53] The impact of GHB on several aspects of sexuality (increased desire and arousal, decreased inhibition, greater willingness to engage in sexual activity) is clearly recognized by all users, but the risk of unsafe sexual practices and sexually transmitted diseases is not appreciated.…”
Section: Gamma-hydroxybutyrate (Ghb)mentioning
confidence: 99%
“…[52] Driving under the influence of GHB and its major consequences are another major point not well recognized by users. [53] The impact of GHB on several aspects of sexuality (increased desire and arousal, decreased inhibition, greater willingness to engage in sexual activity) is clearly recognized by all users, but the risk of unsafe sexual practices and sexually transmitted diseases is not appreciated. [52,54] Interactions between GHB, other recreational drugs and drugs commonly used in the management of HIV-positive patients can occur and may be associated with serious clinical consequences.…”
Section: Gamma-hydroxybutyrate (Ghb)mentioning
confidence: 99%
“…The Web-based survey mentioned above found the following four components: general intoxication (restlessness), negative intoxication (dizzy), negative sexual effects (hard to achieve orgasm), and negative physiological effects (irregular heart beat). Cases of impaired driving have been documented in relation to GHB use (16). Although widely recognized as a “date-rape” drug (13), the widespread use of GHB (or analogs) in commission of sexual assaults has recently been questioned (17).…”
Section: Popular Usementioning
confidence: 99%
“…Many also regard it as a natural part of a subculture in which several different drugs are used [8]. However, a danger of using GHB is related to difficulties dosing it correctly, which leads to a high risk for overdose.…”
Section: Introductionmentioning
confidence: 99%